Multiscale land use impacts on water quality: Assessment, planning, and future perspectives in Brazil. (15th September 2020) - Mello, Kaline de; Taniwaki, Ricardo Hideo; Paula, Felipe Rossetti de; Valente, Roberta Averna; Randhir, Timothy O.; Macedo, Diego Rodrigues; Leal, Cecília Gontijo; Rodrigues, Carolina Bozetti; Hughes, Robert M.
Abstract: Brazil contains the largest volume of freshwater of any nation in the world; however, this essential natural resource is threatened by rapid increases in water consumption and water quality degradation, mainly as a result of anthropogenic pressures. Declining water quality has become an increasingly more significant global concern as economic activities and human populations expand and climate change markedly alters hydrological cycles. Changes in land-use/land-cover (LULC) pattern have been recognized as a major driver of water quality degradation, however different LULC types and intensities affect water quality in different ways. In addition, the relationships between LULC and water quality may differ for different spatial and temporal scales. The increase in deforestation, agricultural expansion, and urban sprawl in Brazil highlights the need for water quality protection to ensure immediate human needs and to maintain the quality of water supplies in the long-term. Thus, this manuscript provides an overview of the relationships between LULC and water quality in Brazil, aiming at understanding the effects of different LULC types on water quality, how spatial and temporal scales contribute to these effects, and how such knowledge can improve watershed management and future projections. In general, agriculture and urban areas are the main LULCs responsible for water quality degradation in Brazil. However, although representing a small percentage of the territory, mining has a high impact on water quality. Water quality variables respond differently at different spatial scales, so spatial extent is an important aspect to be considered in studies and management. LULC impacts on water quality also vary seasonally and lag effects mean they take time to occur. Forest restoration can improve water quality and multicriteria evaluation has been applied to identify priority areas for forest restoration and conservation aiming at protecting water quality, but both need further exploration. Watershed modelling has been applied to simulate future impacts of LULC change on water quality, but data availability must be improved to increase the number, locations and duration of studies. Because of the international nature of watersheds and the consistent relationships between land use and water quality in Brazil, we believe our results will also aid water management in other countries. Graphical abstract: Image 1 Highlights: Agriculture, urbanization and mining are major sources of water quality degradation in Brazil. Water quality variables respond differently to pressures at different spatial scales. LULC impacts on water quality vary seasonally and with varying time lags. Watershed planning and modelling help support decisions but must be improved. Science-based polices and decisions are necessary to protect water quality in Brazil.